First In Situ Seismic Record of Spreading Events at the Ultraslow Spreading Southwest Indian Ridge. Issue 19 (10th October 2018) - Meier, M.; Schlindwein, V.
Abstract: In situ observations of mid‐ocean ridge spreading events are rare, and no observations exist at ultraslow spreading ridges. In 2013, two earthquake swarms and prominent, tidally modulated harmonic tremor were accidentally recorded by ocean bottom seismometers at the Southwest Indian Ridge. After relative relocation, the first swarm shows downward migrating hypocenters, while the second swarm immediately spreads over a steeply dipping plane originating at the same location as the first swarm. The tremor signal is temporally connected to the swarms and persists for more than 20 days after the second swarm. Polarization analysis points to two source locations above the seismically active area at 2‐ to 8‐km depth. We interpret swarms and tremor as evidence for a dike intrusion event that caused disruption to an existent hydrothermal system. The tremor may be generated by enhanced hydrothermal circulation caused by the added heat of the intrusion with increased flow during low tides. Plain Language Summary: At mid‐ocean spreading ridges, tectonic plates drift apart and magma constantly fills the gap between the plates producing fresh seafloor. At the slowest spreading ridges, very little melt is produced and volcanism happens rarely at widely spaced volcanic centers. Seafloor observations of submarine eruptions from these ultraslow spreading ridges do not exist. We instrumented a seismically active volcano on the ultraslow spreading Southwest Indian Ridge with ocean bottom seismometers. The records revealed two small earthquake swarms along with long‐lasting harmonic tremor signals that were strongly influenced by the Earth's tides. We located the source of earthquake swarms and tremor and analyzed their temporal relation. We interpret the migrating earthquake swarms to be caused by moving magma at a depth of about 6 km below the seafloor, heating the area. At the same time water circulates through cracks in the rocks above. The earthquakes may change the water flow paths and the flow is intensified by the heating. This produces the tremor that increases at low tides when the confining water pressure is smaller. Our accidental record of a magmatic spreading event at closest distance shows, for the first time, how magma intrusions drive deep water circulation at ultraslow spreading ridges. Key Points: First seismic in situ record of a spreading event at an ultraslow spreading mid‐ocean ridge Two migrating earthquake swarms indicate downward intrusion of dikes Long‐lasting tidally modulated harmonic seismic tremor potentially caused by enhanced hydrothermal circulation after dike intrusion